STAT3 as a Central Regulator of Tumor Metastases - Devarajan, Eswaran; Huang, Suyun (Current Molecular Medicine, 2009)
Metastasis is a major cause of morbidity and mortality in patients with cancer. The molecular mechanisms that control metastasis are related to alterations in various oncogenes, tumor suppressor genes, metastasis suppressor genes, and growth factors and their receptors. These abnormalities affect the downstream signal transduction pathways involved in the control of cell growth and other malignant properties. One of the most recognized signal transduction pathways involves the signal transducer and activator of transcription 3 (STAT3) protein. STAT3, known to be activated by numerous cytokines, growth factors, and oncogenic proteins, is constitutively phosphorylated in several clinical cancer specimens and cell lines, leading to cell transformation and tumorigenesis. STAT3 target genes are involved in multiple steps of metastasis, including invasion, cell survival, self-renewal, angiogenesis, and tumor-cell immune evasion. Furthermore, the inhibition of STAT3 by a variety of mechanisms can exert anti-tumor and anti-metastasis effects. These findings suggest that STAT3 might be an excellent target for therapeutic intervention in tumor metastases. This review highlights the pivotal role of STAT3 in tumor metastases and in therapeutic strategies to target the STAT3 signaling pathway for the inhibition of metastases.
Keywords: Invasion